Exploring a Band-Edge Bragg Grating Modulator on a Hybrid Thin-Film Lithium Niobate Platform - Xingrui Huang; Yang Liu; Huan Guan; Zhiguo Yu; Manqing Tan; Zhiyong Li (IEEE Photonics Journal)
In this work, we design, model, and characterize the Bragg grating modulator (BGM) on silicon-rich nitride and thin-film lithium niobate (SRN-TFLN) platform. In particular, the slow-light effect on the electro-optical modulation response is modeled and experimentally validated. The presented modulator shows a 3-dB electro-optical (E-O) bandwidth beyond 40 GHz, which agrees well with the simulation results. High-speed modulation up to 60 Gbps and 70 Gbps are experimentally obtained with extinction ratio (ER) of 4.7 dB and 2.7 dB, respectively. A measured modulation efficiency of 2.47 pm/V is also achieved. With optimized slow-light effect and proper design, the proposed BGM has great potential in high-speed data transmission.